Lockdown 101: Managing Economic Lockdowns in an Epidemic - Emanuel Ornelas (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Countries worldwide have implemented lockdown measures to contain the covid-19 pandemic. After more than three months of restrictions to economic activities in many countries, the question has turned to the best ways to lift lockdowns while keeping the epidemic in check. Here I use basic economic principles to shed light on the key tradeoffs. A central message is that there is no “health vs. economics” dichotomy. Rather, some degree of lockdown is typically optimal in crisis like this, balancing its economic costs against its health benefits. Moreover, the optimal lockdown is dynamic, changes over time and eventually becomes more lenient, although the path is not necessarily monotonic.
Keywords: H00; I10; I18; 330; pandemic; covid-19; optimal policies